Love Letters to Planet Earth: A Podcast and Practice for our Planetary Emotional Wellbeing - Anttila, Tessa (Interdisciplinary Journal of Partnership Studies, 2022)
In partnership studies, the configuration of the partnership model supports relations of mutual respect, accountability, and benefit, as well as hierarchies of actualization in which power is employed to empower rather than to disempower others in all relations, from intimate to international. What is possible when this approach is used to address eco-anxiety and pre-traumatic stress related to climate change? This article describes a new podcast and practice designed to nurture partnership with other humans and nature.